Societies, Networks, and Transitions, Volume I: To 1500: A Global History, 4th Edition - Craig A. Lockard (Cengage Learning, 2020)
Exploring history in global framework, Lockard's SOCIETIES, NETWORKS, AND TRANSITIONS, VOLUME l: TO 1500: A GLOBAL HISTORY, Fourth Edition, combines the accessibility and cultural richness of a regional approach with the rigor of comparative scholarship. Emphasizing culture, social change, gender issues, economic patterns, science and religion, it helps you unravel the connections, encounters, cooperation and conflicts of world and regional history. The author includes profiles of individuals from various walks of life as well as highlights social life and cultural artifacts such as music, literature and art. Extensively revised, the text incorporates recent scholarship throughout, examines various debates among historians and explains how historians use original documents. Insightful questions help you reflect on the historical significance of text material -- and how it relates to you. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.